Physical activity during pregnancy and the role of theory in promoting positive behavior change: A systematic review - Erika L. Thompson; Cheryl A. Vamos; Ellen M. Daley (Elsevier, 2017)
Background: Physical activity (PA) during pregnancy provides physical and psychological benefits for mother and child. U.S. guidelines recommend ≥30 min of moderate exercise for healthy pregnant women most days of the week; however, most women do not meet these recommendations. Theory assists in identifying salient determinants of health behavior to guide health promotion interventions; however, the application of theory to examine PA among pregnant women has not been examined cohesively among multiple levels of influence (e.g., intrapersonal, interpersonal, neighborhood/environmental, and organizational/political). Subsequently, this systematic review aims to identify and evaluate the use of health behavior theory in studies that examine PA during pregnancy. Methods: Articles published before July 2014 were obtained from PubMed and Web of Science. Inclusion criteria applied were: (1) empirically-based; (2) peer-reviewed; (3) measured factors related to PA; (4) comprised a pregnant sample; and (5) applied theory. Fourteen studies were included. Each study's application of theory and theoretical constructs were evaluated. Results: Various theories were utilized to explain and predict PA during pregnancy; yet, the majority of these studies only focused on intrapersonal level determinants. Five theoretical frameworks were applied across the studies-all but one at the intrapersonal level. Few determinants identified were from the interpersonal, neighborhood/environmental, or organizational/political levels. Conclusion: This systematic review synthesized the literature on theoretical constructs related to PA during pregnancy. Interpersonal, community, and societal levels remain understudied. Future research should employ theory-driven multi-level determinants of PA to reflect the interacting factors influencing PA during this critical period in the life course.